N-(2,2-Dimethylpropanoyl)-N′-(2-methoxyphenyl)thiourea - Maisara A. Kadir; Bohari M. Yamin; M. Sukeri M. Yusof (Acta Crystallographica Section E, 2012)
In the title compound, C13H18N2O2S, the carbonylthiourea fragment is nearly planar with an r.m.s. deviation of 0.0096 Å. The dihedral angle between carbonylthiourea group and the benzene ring is 19.16 (16)°. There are two intramolecular N—H...O hydrogen bonds, which lead to two pseudo-six-membered rings. Weak intramolecular C—H...S hydrogen bonding also occurs.